Paradoks Feminisasi Pertanian: Waktu, Kontrol Pendapatan, dan Keadilan Nilai dalam Perspektif Intra Rumah Tangga - Wanti Fitrianti; Jajat Sudrajat; Adi Suyatno (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The feminization of agriculture signifies a structural shift in the global agrarian landscape, marked by changing gender dynamics in rural labor and persistent disparities in intra-household resource allocation. This study examines three critical dimensions of this phenomenon time allocation, income control, and value equity within farming households in developing countries. Utilizing a descriptive qualitative approach through a Systematic Literature Review (SLR) of peer-reviewed studies published between 2015-2025, the analysis synthesizes current evidence on gendered labor patterns and decision-making hierarchies.Findings reveal that time allocation is not merely a logistical concern but a reflection of entrenched gendered power relations. Women’s labor is frequently perceived as flexible and inexhaustible, enabling its systematic deployment in low-visibility, undervalued tasks reinforcing structural invisibility and time poverty. Despite increased female engagement in production, processing, and market activities contributing significantly to commercial outputs economic benefits are often redirected under male control, with minimal shift in decision-making authority. This underscores a central paradox: the feminization of labor does not equate to the feminization of power. Instead, agricultural commercialization may intensify the exploitation of women’s labor by integrating it into value chains without equitable returns.Consequently, women face escalating workloads without commensurate enhancements in autonomy or well-being. A persistent inequity in recognition persists: women’s time, skills, and contributions are rarely translated into rights over income, assets, or public acknowledgment. Within household dynamics, this manifests as an unequal sharing of domestic responsibilities, further constraining women’s opportunities for education, health, and economic advancement.Thus, the feminization of agriculture, absent transformative interventions, risks entrenching gendered inequalities rather than fostering empowerment. Sustainable rural development requires policies that challenge asymmetrical labor valuation, redistribute care burdens, and ensure equitable control over resources.